Investigating Students’ Perceptions of Motivating Factors of Online Class Discussions - Lee, Joohi; Martin, Lesisa (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
One of the goals of teacher education is to prepare our citizens to communicate in a variety of ways. In our present society, communication using digital media has become essential. Although online discussions are a common component of many online courses, engaging students in online discussions has been a challenge. This study queried 86 educators in a math/science teacher education graduate program to examine their perceptions on the factors that motivate them to participate in online discussions.The results revealed a pragmatic outlook on online education. In terms of intrinsic versus extrinsic motivation, the participants’ main motivation to participate in online class discussions was extrinsic (85.88%), specifically so that they could earn an acceptable participation grade. With regards to discussion grouping formats, they preferred small group discussions (81%) which could facilitate their ability to develop rapport with a small group of fellow classmates over whole class discussion (38.83%). With respect to discussion facilitation, they focused on the practical need to have the instructor to answer their questions about course assignments (67.06%) over online open discussion without a given topic (35.72%). Next, when asked about discussion question types based on Bloom’s taxonomy, their strongest preference reflected a desire for application (89.54%) questions which would facilitate their ability to use theories discussed in class in their daily work as educators. Through collaboration with twenty-first-century learners, online education can use data-driven decision making to help transform online discussion from being the least desirable component of online courses to a more relevant, instructional medium.